Water–Energy–Food nexus modeling: A fad or the future? - Holmatov, Bunyod; Davies, Stephen; Ringler, Claudia (CGIAR, 2023)
This session from Pakistan Water Week 2023 underscores the merits of employing integrated modeling frameworks by presenting a series of enlightening country case studies from the CGIAR Initiative on NEXUS Gains. A panel also discusses how best to align scientific insights with policymaking and enhance collaboration to tackle climate extremes and secure the future of these critical systems. The goal is to enhance water, food, energy, and environmental outcomes, especially given the escalating challenges posed by climate extremes.